The Usage of Colligations of Preposition Among Malaysian Law Undergraduates: A Need Analysis - Kamariah, Yunus; Su'ad, Awab (2014)
Needs analyses carried out among Malaysian law undergraduates, particularly those investigating the students’ lack of competence in legal English, are rare. This paper aimed to investigate Malaysian law undergraduates’ perceptions and usage of colligations of prepositions, one of the most essential lexico-grammatical components in legalese. 40 third semester Malay law undergraduates from one public university participated in the study. Two types of data were collected for this purpose - an interview and essay writing test. Eight out of the 40 students participated in the interview, while all respondents took the essay test conducted a week later. The interview responses were analysed manually, and Dulay et al.’s (1982) Surface Strategy Taxonomy was employed in the analysis of the subjects’ production of prepositional patterns in the Problem Question essays (of legal contract genre). The results from the interviews and essays demonstrate that the subjects lack knowledge of prepositions and their patterns, resulting mainly from interlingual (L1 negative transfer, i.e. Malay) and intralingual (difficulty with the L2 itself, i.e. legalese) interference, as well as the drilling methods applied in both primary and secondary schools. More needs analyses should be carried out in a specialised field like law in future for the short-term and long-term benefits of the students. While both English and law lecturers may gain feedback on their students’ current lexico-grammatical competence, whereby some actions can be taken to improve performance, the results from the analysis may help in developing materials for ELAP (English for Legal Academic Purposes) courses, or in establishing an ELAP course, especially if the course has not yet been established in the institutions offering law programmes.